2020
DOI: 10.3390/rs12152455
|View full text |Cite
|
Sign up to set email alerts
|

Flood Detection Using Multi-Modal and Multi-Temporal Images: A Comparative Study

Abstract: Natural disasters such as flooding can severely affect human life and properties. To provide rescue through an emergency response team, we need an accurate flooding assessment of the affected area after the event. Traditionally, it requires a lot of human resources to obtain an accurate estimation of a flooded area. In this paper, we compared several traditional machine learning approaches for flood detection including multilayer perceptron (MLP), support vector machine (SVM), deep convolutional neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 38 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The classification is carried out on a post-event SAR acquisition. An interesting comparative study on the performance of ML and DL frameworks has been proposed in [123].…”
Section: Other Methodologies 351 Multi-sensor Data Fusionmentioning
confidence: 99%
“…The classification is carried out on a post-event SAR acquisition. An interesting comparative study on the performance of ML and DL frameworks has been proposed in [123].…”
Section: Other Methodologies 351 Multi-sensor Data Fusionmentioning
confidence: 99%
“…Similarly, in [10], images from both Sentinel-1 and Sentinel-2, as well as CNN models, are used to detect floods in these images, achieving an accuracy of 80%. Furthermore, [11] compares several machine learning algorithms (neural networks and SVM) with CNNs for flood detection in radar images. In [12], the performance of a multi-modal model that integrates a CNN with a transformer is compared with that of singular models, such as random forest, neural network, SVM, and CNN.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning [1,2] and deep learning [3,4] They evaluated the performance of the models using the Sentinel-1 images. Using several machine learning methods including MLP, SVM, and a deep neural network (DNN), Islam et al [10] identified flood areas in SPOT-5 and radar image sets. Tanim et al [11] evaluated the performance of supervised and unsupervised machine learning models including Random Forest, SVM, and Maximum Likelihood using Sentinel-1 satellite images.…”
Section: Introductionmentioning
confidence: 99%